Supernatural, social, and self-monitoring in the scaling-up of Chinese civilization - Sarkissian, Hagop (Religion, brain & behavior, 2015)
This commentary evaluates Ara Norenzayan's central thesis in Big Gods: How Religion Transformed Cooperation and Conflict, focusing on how it bears on the rise of early Chinese civilization. Discussion centers on three themes: supernatural monitoring, social monitoring, and self-monitoring.